Stability analysis of heterogeneous oligopoly games of increasing players: A computational approach - Ruirui Hou; Xiaoliang Li; Wenshuang Wan (PLoS ONE, 2025)
In this paper, we study an oligopolistic market endowed with an isoelastic demand function and a quadratic cost function, where heterogeneous firms coexist and produce the same product. We create new games by adding additional heterogeneous firms one after the other, and we examine the relative size of the stability region as the number of heterogeneous firms increases. For each model studied, we use the cylindrical algebraic decomposition method to analytically investigate the conditions for the local stability of the Cournot–Nash equilibrium. We find that the stability regions become larger as the number of heterogeneous firms involved increases. We also perform numerical simulations to investigate complex dynamics, such as periodic orbits and chaos, when the equilibrium loses its stability. Furthermore, we investigate the case of distinct cost parameters through numerical simulations and find that the dynamics seem more complicated than the case of identical cost parameters.